2020
DOI: 10.26444/aaem/118228
|View full text |Cite
|
Sign up to set email alerts
|

Chromium (III) and chromium (VI) as important players in the induction of genotoxicity – current view

Abstract: Sawicka E, Jurkowska K, Piwowar A. Chromium (III) and chromium (VI) as important players in the induction of genotoxicity-current view. Ann Agric Environ Med.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 69 publications
1
30
0
Order By: Relevance
“…Cr (III) can cause genetic effects when specifically confronted with purified nucleic or subcellular targets, however, when Cr (III) compound was tested in cellular system, this potential genotoxic capacity was lost (Sawicka et al, 2020; Silvio et al, 1989). Cr (VI) intracellularly reduces into Cr (III) with the latter forming potentially genotoxic complexes with DNA (Jomova and Valko, 2011; O’Flaherty et al, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…Cr (III) can cause genetic effects when specifically confronted with purified nucleic or subcellular targets, however, when Cr (III) compound was tested in cellular system, this potential genotoxic capacity was lost (Sawicka et al, 2020; Silvio et al, 1989). Cr (VI) intracellularly reduces into Cr (III) with the latter forming potentially genotoxic complexes with DNA (Jomova and Valko, 2011; O’Flaherty et al, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…Cr(VI) does not directly interact with DNA, but the genotoxicity of Cr(VI) is rather attributed to its intracellular reduction to Cr(III) via reactive intermediates. The products from the reaction such as ROS, Cr (V), and Cr (IV) are potential sources of oxidative damage induced by Cr(VI) which can lead to two types of DNA damage namely, oxidative damage and Cr(III)-DNA interactions which proceeded via a three-step cross-linking mechanism, i.e., reduction of Cr(VI) to Cr(III), binding of Cr(III) to DNA binding, and protein capture by DNA-bound Cr(III) generating protein-Cr(III)-DNA cross-links [16,17].…”
Section: Cytotoxicity and Genotoxicity Of Crmentioning
confidence: 99%
“…Chromium is commonly used for the production of steel and other alloys, bricks, dyes and pigments, leather tanning, electroplating and wood preserving [1]. It was reported that occupational exposure to trivalent chromium can lead to oxidative stress and DNA damage in tannery workers [2]. Due to extensive use in industrial processes, large quantities of Cr compounds are discharged into the environment and contaminate the air, soil, surface water and groundwater.…”
Section: Introductionmentioning
confidence: 99%